Conservation of heritage areas - Bajracharya, Sujata (Journal of Innovations in Engineering Education, 2019)
Conservation and heritage areas both are very sensible and important for any nation. For our country, Nepal, it is more important asit has lots of national and international heritage areas and have to conserve as much as possible in a suitable and best way. As one should know the typical type of process which can be followed as required by any heritage area. To conserve the heritage area, one may follow one or more than one process for same project. According to international conservation pattern or rules, here comes few types of conservation ways which may be fitted for our context too.